2009
DOI: 10.1007/s00221-009-1995-y
|View full text |Cite
|
Sign up to set email alerts
|

Practice-related improvements in posture control differ between young and older adults exposed to continuous, variable amplitude oscillations of the support surface

Abstract: Healthy older adults were repeatedly exposed to continuous, variable amplitude oscillations of the support surface to determine 1) whether age affects the capacity for postural motor learning under continuous perturbation conditions with limited predictability and 2) whether practice leads to modifications in the control strategy used to maintain balance in older adults. During training, a translating platform underwent 45-second trials of constant frequency (0.5 Hz) and seemingly random amplitude oscillations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
3
46
0
1
Order By: Relevance
“…Participants in this study were healthy older adults with no known problems with balance. Other studies among healthy older adults reported improved performance and learning with practice of standing on a moving platform using similar pseudo-random waveforms to those used in the current study (Van Ooteghem et al 2009;Van Ooteghem et al 2010). However, it is possible that, for participants in the current study, the task was not sufficiently challenging for participants to show improvement throughout the acquisition period.…”
Section: Discussionsupporting
confidence: 58%
“…Participants in this study were healthy older adults with no known problems with balance. Other studies among healthy older adults reported improved performance and learning with practice of standing on a moving platform using similar pseudo-random waveforms to those used in the current study (Van Ooteghem et al 2009;Van Ooteghem et al 2010). However, it is possible that, for participants in the current study, the task was not sufficiently challenging for participants to show improvement throughout the acquisition period.…”
Section: Discussionsupporting
confidence: 58%
“…This finding supports the hypothesis that ABF resulted in significant postural motor learning during the experiment, resulting in motor retention even in control trials without ABF. However, as Van Ooteghem et al [13] recently showed, improvements in postural control including change of postural strategy may occur also as a consequence of pure spontaneous learning.…”
Section: Discussionmentioning
confidence: 94%
“…It is not clear how specific biofeedback should be (amplitude and/or direction or alarm threshold) to maximize improvement in sway during stance. It is often difficult to determine how much postural stability benefits from biofeedback since it is always superimposed upon a large practice effect due to spontaneous motor learning [13]. In this study, we evaluate the effects of different types of postural sway information from ABF and the interaction between improvements from ABF and spontaneous motor learning during perturbed stance.…”
mentioning
confidence: 97%
“…The postural disturbance evoked by anteroposterior floor oscillations is periodic and continuous. Subjects can acquire sensory information and anticipate the postural disturbance associated with the floor oscillation, and can therefore easily improve postural stability [26][27][28][29] . The improvement is brought by the control of individual body segments with minimum postural muscle activity 30) .…”
Section: Postural Control During Transient Floor Translationsmentioning
confidence: 99%